Green Finance in China - Pulatova Saodat Vokhid qizi (Periodica Journal, 2024)
This article explores the rapid development of green finance in China, examining the country’s strategic shift toward sustainable financial practices in response to growing environmental concerns. With a focus on the evolution of China’s environmental policies, the paper highlights the role of green finance in supporting the nation’s transition to a more sustainable economic model. It discusses various financial instruments such as green bonds, green credit, and the integration of environmental factors into China’s financial markets. Drawing on government reports, statistical data, and academic research, the article provides insights into how China is addressing ecological challenges, such as air pollution and carbon emissions, through financial innovation. It also explores China's commitments to achieving carbon neutrality by 2060 and the role that green finance plays in this endeavor. Through this examination, the paper underscores the importance of aligning financial systems with environmental goals and provides an overview of the country’s approach to fostering a low-carbon economy
Keywords: Green Finance; China; Sustainable Development; Environmental Policy